Growth tradeoffs produce complex microbial communities on a single limiting resource - Michael Manhart (Nature Portfolio, 2018)
Higher-order interactions occur when one species mediates the interaction between two others. Here, the authors model microbial growth and competition to show that higher-order interactions can arise from tradeoffs in growth traits, leading to neutral coexistence and other complex dynamics.